Strategies to Improve Capacity for Policy Monitoring and Evaluation in the Public Sector - Matsiliza, N.S. (Journal of Reviews on Global Economics, 2018)
Scholars around the globe have contested the inadequate infrastructure and tools used by public sector agencies to monitor and evaluate public policies and programmes. Some of the urgent issues of concern deal with the inadequate human capacity in public agencies and departments to conduct fair and credible evaluations in the public sector. South Africa is not the only country that has adopted a government wide monitoring and evaluation system, other countries like Ghana, Kenya, Benin and Uganda have also endorsed formal monitoring and evaluation practice in the public sector. This article argues that monitoring and evaluation must not just measure the effectiveness and efficiency of public programmes and processes, but it must create a sustainable process whereby participants and evaluators can learn from the process. Capacity building in monitoring and evaluation must be fairly and continuous conducted to offer credible and valid information and knowledge on M&E by training agencies and institutions like universities. This theoretical paper adopted document analysis strategy to review and evaluate documents used as data source. Lessons learnt from this article contribute towards the existing strategies to enhance monitoring and evaluation.